Organoids: opportunities and challenges of cancer therapy - Jiang, Xianjie; Oyang, Linda; Peng, Qiu; Liu, Qiang; Xu, Xuemeng; Wu, Nayiyuan; Tan, Shiming; Yang, Wenjuan; Han, Yaqian; Lin, Jinguan; Xia, Longzheng; Peng, Mingjing; et al. (Frontiers in Cell and Developmental Biology, 2023)
Organoids are a class of multicellular structures with the capability of selforganizing and the characteristic of original tissues, they are generated from stem cells in 3D culture in vitro. Organoids can mimic the occurrence and progression of original tissues and widely used in disease models in recent years. The ability of tumor organoids to retain characteristic of original tumors make them unique for tumorigenesis and cancer therapy. However, the history of organoid development and the application of organoid technology in cancer therapy are not well understood. In this paper, we reviewed the history of organoids development, the culture methods of tumor organoids establishing and the applications of organoids in cancer research for better understanding the process of tumor development and providing better strategies for cancer therapy. The standardization of organoids cultivation facilitated the largescale production of tumor organoids. Moreover, it was found that combination of tumor organoids and other cells such as immune cells, fibroblasts and nervous cells would better mimic the microenvironment of tumor progression. This might be important developing directions for tumor organoids in the future.